Interaction of St John's wort with conventional drugs: systematic review of clinical trials. Issue 7456 (1st July 2004) - Mills, Edward; Montori, Victor M; Wu, Ping; Gallicano, Keith; Clarke, Mike; Guyatt, Gordon
Abstract: Objective To determine the methodological quality of clinical trials that examined possible interactions of St John's wort with conventional drugs, and to examine the results of these trials. Design Systematic review. Data sources Electronic databases from inception to April 2004, reference lists from published reports, and experts in the field. Study selection Eligible studies were prospective clinical trials evaluating the pharmacokinetic effect of St John's wort on the metabolism of conventional drugs. Data extraction Two reviewers selected studies for inclusion and independently extracted data. Data synthesis 22 pharmacokinetic trials studied an average of 12 (SD 5) participants; 17 trials studied healthy volunteers and five studied patients. Most (17) studies used a "before and after" design; four studies used control groups other than the active group. Three studies randomised the sequence of administration or the participants to study arms or periods; three studies blinded participants or investigators. In 15 trials, investigators independently assayed the herb. Of 19 trials with available plasma data, three found no important interaction (change in area under the curve < 20%) and 17 found a decrease in systemic bioavailability of the conventional drug; in seven studies the 95% confidence interval excluded a decrease of < 20%. Conclusion Clinicians and patients should beware of possible decreases in the systemic bioavailability of conventional drugs when taken concomitantly with St John's wort.